Differential of Frequency and Duration Mismatch Negativity and Theta Power Deficits in First-Episode and Chronic Schizophrenia - Xiong, Yan-Bing; Bo, Qi-Jing; Wang, Chang-Ming; Tian, Qing; Liu, Yi; Wang, Chuan-Yue (Frontiers in Behavioral Neuroscience, 2019)
Background: As mismatch negativity (MMN) generation is impaired in patients with schizophrenia, it has been identified as a potential biomarker for identifying primary impairments in the auditory sensory processing. This study aimed to investigate the dysfunctional differences in different MMN deviants and theta evoke power in patients with first-episode schizophrenia and chronic schizophrenia. Methods: We measured frequency and duration MMN from 40 first-episode schizophrenia patients, 40 chronic schizophrenia patients, and 40 healthy controls. Theta power was analyzed by event-related spectral perturbation (ERSP) approaches. Results: Deficits in duration MMN were observed in both first-episode (p = 0.009, Bonferroni-adjusted) schizophrenia and chronic schizophrenia patient groups (p < 0.001, Bonferroni-adjusted), nevertheless, the deficits in frequency MMN were restricted to the chronic schizophrenia group (p < 0.001, Bonferroni-adjusted). Theta power deficits were observed in both patient groups when compared with the healthy controls (pFES = 0.001, pCS < 0.001, Bonferroni-adjusted), yet no significant differences were found between the two patient groups. The frequency MMN deficits were correlated with the MCCB combined score (r = -0.327, p < 0.05) and MCCB verbal learning (r = -0.328, p < 0.05) in first-episode schizophrenic patients. Theta evoke power deficits were correlated with MCCB working memory in both first-episode schizophrenic patients (r = 0.347, p < 0.05) and chronic schizophrenic patients (r = 0.408, p < 0.01). Conclusion: These findings suggest that duration MMN and theta power deficits may be more sensitive for detection of schizophrenia during the early stages of schizophrenia. Moreover, frequency MMN and theta power deficits could be potentially linked to poor cognitive functioning in schizophrenic patients.